Hypocrisy, ‘Prudence’, ‘Conscience’ in Administration: The Congregation of Bishops and Regulars in Seventeenth-Century Italy - Maghenzani, Simone (Studies in church history, 2024)
The article argues that the post-Tridentine papacy was more focused on maintaining its own centrality than on implementing the reforms established by the Council of Trent. It shows that the Roman Curia often undermined its own bishops and interfered with their efforts to reform their dioceses. This practice - which might be perceived as hypocritical by us and was viewed as such by some contemporary commentators - was seen as justified by the baroque political virtue of ‘prudence’, and the idea of bishops being the conscience keepers of their dioceses. The article, in pondering the theme of hypocrisy, explores the work of the Sacred Congregation of Bishops and Regulars, which was responsible for overseeing the episcopate and religious orders. It uses previously unnoticed sources from the Bodleian Library in Oxford to show how the Congregation operated and how it perceived its role in defending the rights of the church and its clergy.